PENGARUH DUKUNGAN SOSIAL DAN KECERDASAN EMOSIONAL PADA HASIL BELAJAR MATA DIKLAT PRODUKTIF AKUNTANSI SISWA SMK SUNAN DRAJAT LAMONGAN - Supriyati, Supriyati (UNIVERSITAS NEGERI SURABAYA, 2014)
This research purposed to examine the influence of social support and emotional intelligence on the results of the studying accounting subject. The populations of the research are the students of SMK Sunan Drajat Lamongan, accounting Expertise Program that consist of 174 with a sample of 122 students and it was using proportional random sampling. The Technique of data collecting using based on documents, observation and questionnaires. The data analysis uses multiple linear regression, in partial there are influence between social support and learning outcomes between emotional intelligence and learning outcomes and in simultaneously œthere are the influence of social support and emotional intelligence with learning outcomes